Dapagliflozin and New York Heart Association functional class in heart failure with mildly reduced or preserved ejection fraction: the DELIVER trial. (27th August 2022) - Ostrominski, John W.; Vaduganathan, Muthiah; Claggett, Brian L.; de Boer, Rudolf A.; Desai, Akshay S.; Dobreanu, Dan; Hernandez, Adrian F.; Inzucchi, Silvio E.; Jhund, Pardeep S.; Kosiborod, Mikhail; Lam, Carolyn S.P.; Langkilde, Anna M.; et al.
Abstract : Aims: This pre‐specified analysis of the DELIVER trial examined whether clinical benefits of dapagliflozin in heart failure (HF) with left ventricular ejection fraction (LVEF) >40% varied by baseline New York Heart Association (NYHA) class and examined the treatment effects on NYHA class over time. Methods and results: Treatment effects of dapagliflozin by baseline NYHA class II ( n  = 4713) versus III/IV ( n  = 1549) were examined on the primary endpoint (cardiovascular death or worsening HF event) and key secondary endpoints. Effects of dapagliflozin on change in NYHA class at 4, 16, and 32 weeks were also evaluated. Higher baseline NYHA class was associated with older age, female sex, greater comorbidity burden, lower LVEF, and higher natriuretic peptide levels. Participants with baseline NYHA class III/IV, as compared with II, were independently more likely to experience the primary endpoint (adjusted hazard ratio [HR] 1.16 [95% confidence interval, 1.02–1.33]) and all‐cause death (adjusted HR 1.22 [1.06–1.40]). Dapagliflozin consistently reduced the risk of the primary endpoint compared with placebo, irrespective of baseline NYHA class (HR 0.81 [0.70–0.94] for NYHA class II vs. HR 0.80 [0.65–0.98] for NYHA class III/IV; p interaction  = 0.921). Participants with NYHA class III/IV had greater improvement in Kansas City Cardiomyopathy Questionnaire total symptom scores between baseline and 32 weeks (+4.8 [2.5–7.1]) versus NYHA class II (+1.8 [0.7–2.9]; p interaction  = 0.011). Dapagliflozin was associated with higher odds of any improvement in NYHA class (odds ratio [OR] 1.32 [1.16–1.51]), as well as improvement to NYHA class I (OR 1.43 [1.17–1.75]), versus placebo at 32 weeks, with benefits seen as early as 4 weeks. Conclusions: Among symptomatic patients with HF and LVEF >40%, treatment with dapagliflozin provided clinical benefit irrespective of baseline NYHA class and was associated with early and sustained improvements in NYHA class over time. Abstract : Summary of clinical profiles and treatment effects of dapagliflozin by baseline New York Heart Association (NYHA) class, as well as the impact of dapagliflozin on changes in NYHA class over time in this pre‐specified analysis of the DELIVER trial. CI, confidence interval; DELIVER, Dapagliflozin Evaluation to Improve the Lives of Patients with Preserved Ejection Fraction; HF, heart failure; HFmrEF, heart failure with mildly reduced ejection fraction; HFpEF, heart failure with preserved ejection fraction; KCCQ, Kansas City Cardiomyopathy Questionnaire; LVEF, left ventricular ejection fraction; NT‐proBNP, N‐terminal pro‐B‐type natriuretic peptide; OR, odds ratio.